Genetic signatures in choline and 1‐carbon metabolism are associated with the severity of hepatic steatosis. Issue 4 (4th January 2013) - Corbin, Karen D.; Abdelmalek, Manal F.; Spencer, Melanie D.; da Costa, Kerry‐Ann; Galanko, Joseph A.; Sha, Wei; Suzuki, Ayako; Guy, Cynthia D.; Cardona, Diana M.; Torquati, Alfonso; Diehl, Anna Mae; Zeisel, Steven H.
Abstract : Choline metabolism is important for very low‐density lipoprotein secretion, making this nutritional pathway an important contributor to hepatic lipid balance. The purpose of this study was to assess whether the cumulative effects of multiple single nucleotide polymorphisms (SNPs) across genes of choline/1‐carbon metabolism and functionally related pathways increase susceptibility to developing hepatic steatosis. In biopsy‐characterized cases of nonalcoholic fatty liver disease and controls, we assessed 260 SNPs across 21 genes in choline/1‐carbon metabolism. When SNPs were examined individually, using logistic regression, we only identified a single SNP ( PNPLA3 rs738409) that was significantly associated with severity of hepatic steatosis after adjusting for confounders and multiple comparisons ( P =0.02). However, when groupings of SNPs in similar metabolic pathways were defined using unsupervised hierarchical clustering, we identified groups of subjects with shared SNP signatures that were significantly correlated with steatosis burden ( P =0.0002). The lowest and highest steatosis clusters could also be differentiated by ethnicity. However, unique SNP patterns defined steatosis burden irrespective of ethnicity. Our results suggest that analysis of SNP patterns in genes of choline/1‐carbon metabolism may be useful for prediction of severity of steatosis in specific subsets of people, and the metabolic inefficiencies caused by these SNPs should be examined further.—Corbin, K. D., Abdelmalek, M. F., Spencer, M. D., da Costa, K.‐A., Galanko, J. A., Sha, W., Suzuki, A., Guy, C. D., Cardona, D. M., Torquati, A., Diehl, A. M., Zeisel, S. H. Genetic signatures in choline and 1‐carbon metabolism are associated with the severity of hepatic steatosis. FASEB J. 27, 1674–1689 (2013). www.fasebj.org